(untitled) (Modern education and development, 2025)
Stereotypes are widely held but fixed and oversimplified beliefs about specific groups of people.While they may seem harmless, stereotypes can reinforce social inequalities, limit individual potential, and contribute to discrimination. This article explores the origins of stereotypes, their psychological and social effects, and possible strategies to overcome them. By understanding the mechanisms behind stereotypes, societies can work towards more inclusive and fair interactions